Synthesis of α-Hydroxy Acids via Dehydrogenative Cross-Coupling of a Sustainable C2 Chemical (Ethylene Glycol) with Alcohols - Lee, Mi Hyun; Byeon, Heemin; Jang, Hye Young (Journal of Organic Chemistry, 2022)
Ir(NHC) (NHC, N-heterocyclic carbene)-catalyzed dehydrogenative coupling of sustainable ethylene glycol and various bioalcohols can produce industrially valuable α-hydroxy acids (AHAs). This study is the first to report the sustainable synthesis of higher Cn AHAs, in addition to glycolic acid (C2 AHA) and lactic acid (C3 AHA). This catalytic system can be recycled to the seventh cycle while maintaining good yields. A reaction mechanism, including facile dehydrogenation of each alcohol and fast cross-coupling of dehydrogenated aldehydes forming products, was proposed based on 18O- and 2H-labeling experiments and electron spray ionization-mass spectrometry (ESI-MS) and NMR spectral analyses.
Keywords: Catalytic system; Cross-couplings; Dehydrogenative coupling; Glycolic acids; Hydroxy acids; Ionization mass spectrometry; Labelings; N-heterocyclic carbenes; Reaction mechanism; Spray ionization